Design of Automatic Candy Mixer using Blynk and NodeMCU ESP8266 - Hugeng Hugeng; Khefin Khefin; Meirista Wulandari (Tecno Scientifica Publishing, 2022)
Candy has many variations based on shape, texture, and taste. The more variations of the product have an effect on more consumers, Candy products also have a lot of variety, which makes mixing candy an interesting task. The mixing process of candies is usually done by weighting them manually with conventional scales, so there are some deficiencies to be improved. The automatic candy mixer using Blynk and NodeMCU ESP8266 has been designed to be able to help with the process of mixing and weighting candy automatically. This device allows users to choose weight and candy types to be mixed, whether it is one type of candy or more, from the Blynk application and is operated using a microcontroller and sensor. The utilized sensor is a load cell sensor with 1% of calibration inaccuracy.